IT capabilities, firm performance and the mediating role of ISRM: A case study from a developing country. Issue 3 (27th June 2019) - Kala Kamdjoug, Jean Robert; Nguegang Tewamba, Harold Junior; Fosso Wamba, Samuel
Abstract : Purpose: The purpose of this paper is to develop and test a research model that looks at the direct impact of information technology (IT) capabilities on firm performance and the mediating effects of the information security management system (ISMS) on this relationship. Design/methodology/approach: The study uses a hypothetico-deductive approach based on quantitative data collected from 136 surveyed professionals in the field of IS, IT and the related security environment. Findings: The results confirm the direct impact of IT capabilities on firm performance and the mediating effects of ISMS on this relationship. Originality/value: The study draws on the resource-based view theory to develop a model that assesses the direct impact of IT capabilities on firm performance and the mediating effects of ISMS on this relationship in Cameroon, a developing country in Africa.